Livros impressos versus eletrônicos: análise de custo-benefício para as Universidades federais no Brasil - Leber, Andreas [UNIFESP] (2015)
The purpose of this dissertation is to identify the most active publishers and e-book suppliers in the Libraries of Federal Universities, their business models and the challenges that their managers face in the use of those ones by the University Libraries, from legal and regulatory challenges up to challenges posed by the market and by the users. Data collection was carried out from a questionnaire sent to ten Brazilian federal universities, two universities by Brazilian geographic region. From the data collected, the most widely used model is the perpetual access, followed by subscription. In addition, by annual statistical comparison of loans of printed book , it was noted that e-books are accepted and used by users of the federal university libraries. It was found that most users still find it difficult to grasp the electronic content in the same manner as they do with the printed one by cognitive reasons and, therefore, the hybrid model is best suited for libraries with digital and electronic collections.